Yogurt-like Product from Fermented Maize Part I: Selection of Starter and Fermentation Conditions - Nguyen, Tien Cuong; Le, Thi Thanh Tam; Nguyen, Thi Yen; Luong, Hong Nga (Old Journal, 2017)
Fermented starchy foods and beverages play an important role in the diet of many countries. Maize is used as the main raw material and considered as non-allergenic food. This study focussed on the selection of lactic starter and fermentation conditions in order to control product quality. Six single lactic acid bacteria were inoculated in maize suspension (20% dry matter content). The cell density varied between $10^{5}$ and $10^{7}CFU.mL^{-1},$ the fermentation temperature ranged from 26 to $42^{°}C$ during 18h. Different biochemical and sensorial characteristics were evaluated. The results showed that Lactobacillus plantarum NCDN4 is the most suitable strain for production of yogurt-like beverage. The used cell density was $10^{6}CFU.mL^{-1}$ and fermentation occurred at $32^{°}C$ for 12h. Final obtained product was biochemically comparable to popular drinking yogurt with pH $4.23±0.03$, titratable acidity $2.83±0.03$ (g lactic acid.L-¹) with desirable taste, texture and aroma.